Crystallization promoting type self-healing concrete admixture
By using crystallization-promoting self-healing concrete admixtures in concrete, the deficiencies of crystallization admixtures in improving self-healing properties are solved, achieving more efficient self-healing of cracks and long-term effectiveness.
Patent Information
- Application Number
- CN202411511573.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-21
AI Technical Summary
When existing crystallization admixtures improve the self-healing properties of concrete, there are problems such as limited reactants, slow reaction process and fuzzy long-term effectiveness.
A crystallization-promoting self-healing concrete admixture is used, including ionic complexing agent, calcium formate, silica sol and dispersible latex powder, to improve the self-healing performance of concrete by increasing the concentration and reaction rate of self-healing reactants. .
It effectively improves the self-healing performance of concrete materials, making cracks above 0.4mm completely self-healing, extending the effectiveness of self-healing behavior, and is suitable for concrete structures lasting more than 600 days.
Smart Images

Figure CN119330628A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of civil engineering materials, and in particular to a crystallization-promoting self-healing concrete admixture. Background Art
[0002] Concrete materials have the advantages of high strength, low cost, and easy access to raw materials. They are the most widely used building materials in the world. However, under the influence of external loads, environment and other factors, cracks will inevitably appear in concrete materials during their service life, accelerating the erosion of harmful ions in the external environment, thus causing serious degradation of the performance of the concrete structure. In an environment rich in chloride ions, cracks will cause the steel bars inside the concrete structure to rust quickly. Severe steel corrosion can even cause the concrete structure to change from a ductile failure mode to a brittle failure mode. Therefore, in order to solve the problems of durability and bearing capacity degradation of concrete structures caused by cracks, timely repair of concrete cracks becomes the key.
[0003] The inherent self-healing ability of concrete can actively and timely repair the damaged cracked locations, which is not only expected to solve the problems of structural performance degradation caused by erosion by harmful substances, but also to restore the use function of concrete structures, providing a new guiding direction for solving the difficulties of construction projects caused by crack repair. However, the limited source of self-healing products limits the width of cracks that can be healed by the concrete material itself, thereby affecting the potential of concrete self-healing performance to improve the durability and safety of cracked concrete structures. Therefore, it is necessary to optimize and explore self-healing materials that improve the self-healing performance of concrete.
[0004] The optimization research on the self-healing properties of concrete materials is ultimately aimed at giving concrete structures good self-healing properties. Compared with concrete materials, concrete structures have higher requirements on the quantity, cost, construction technology and application environment of self-healing materials. At present, due to their respective healing mechanisms, self-healing materials commonly used to improve the self-healing properties of concrete materials are subject to many restrictions in their application in concrete structures, such as easy rupture of microcapsules and difficulty in ensuring healing efficiency; high survival rate of microorganisms and high cost; high energy consumption and high cost of shape memory alloys. Crystallized admixtures can be directly mixed with concrete materials for use, and the construction is simple and low-cost. Therefore, compared with other self-healing technologies, crystalline admixtures have good application potential for concrete structures. Summary of the invention
[0005] The present invention provides a promoted crystallization type self-healing concrete admixture to address the technical defects of the crystalline admixture, such as the limited number of self-healing reactants, the slow progress of the self-healing reaction, and the unclear long-term effectiveness. The admixture provided by the present invention has an ion complexing agent as a core component, and by increasing the concentration of the self-healing reactants and the self-healing reaction rate, it effectively solves the problems of the slow speed and small width of the crystalline admixture in improving the healing cracks in concrete, and the difficulty in ensuring the long-term effectiveness.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] On the one hand, the present invention provides a crystallization-promoting self-healing concrete admixture, which comprises, by weight, 485-520 parts of an ion complexing agent, 2370-2380 parts of calcium formate, 4740-4760 parts of silica sol and 2370-2380 parts of dispersible latex powder.
[0008] As a preferred embodiment, the ion complexing agent is 20 to 30 parts of sodium hexametaphosphate and 465 to 490 parts of tetrasodium ethylenediaminetetraacetate.
[0009] As a preferred embodiment, the silica sol is an alkaline nano-scale silica solution, wherein the content of silica is 30±1%.
[0010] As a preferred embodiment, the dispersible latex powder is ethylene-vinyl acetate copolymer;
[0011] In some specific embodiments, the molar ratio of ethylene to vinyl acetate in the ethylene-vinyl acetate copolymer is 1:1.
[0012] On the other hand, the present invention provides a crystallization-promoting self-healing cement-based composite material, which comprises, by weight, 2300 to 2400 parts of cement, 80 to 300 parts of the above-mentioned crystallization-promoting self-healing concrete admixture, 3000 to 4000 parts of fly ash, 2000 to 2200 parts of fine aggregate, 30 to 35 parts of water reducer and 120 to 130 parts of polyvinyl alcohol fiber.
[0013] As a preferred embodiment, 1700 to 1800 parts of water are also included.
[0014] As a preferred embodiment, the water reducer is a polycarboxylate water reducer.
[0015] As a preferred embodiment, the cement is ordinary Portland cement.
[0016] In another aspect, the present invention provides a method for preparing the above-mentioned promoted crystallization self-healing cement-based composite material, comprising the following steps:
[0017] (1) mixing the powdered raw materials in the above-mentioned crystallization-promoting self-healing concrete admixture with cement, fly ash and fine aggregate;
[0018] (2) adding a mixture of water and silica sol and a water reducing agent, and stirring until the mixture is in a uniform fluid state;
[0019] (3) Add polyvinyl alcohol fibers under low-speed stirring and stir rapidly until they are evenly dispersed.
[0020] As a preferred embodiment, in step (1), the stirring is revolution 65±5r / min and rotation 145±5r / min;
[0021] Preferably, the stirring time is 2 to 4 minutes.
[0022] As a preferred embodiment, in step (2), the stirring is revolution 130±5 r / min and rotation 290±5 r / min.
[0023] Preferably, the stirring time is 2 to 4 minutes.
[0024] As a preferred embodiment, in step (3), the low-speed stirring is revolution 65±5 r / min and rotation 145±5 r / min; the fast stirring is revolution 130±5 r / min and rotation 290±5 r / min;
[0025] Preferably, the low-speed stirring time is 2 to 3 minutes; the fast stirring time is 5 to 8 minutes.
[0026] In another aspect, the present invention provides use of the above-mentioned crystallization-promoting self-healing concrete admixture in preparing a self-healing cement-based composite material.
[0027] The present invention has the following advantages and beneficial effects:
[0028] In the prior art, commercialized crystallization admixtures have limited improvement on the self-healing performance of concrete materials, mainly in terms of the width of healable cracks and the improvement of the healing speed. The promoted crystallization self-healing concrete admixture provided by the present invention, calcium formate and silica sol can increase the concentration of reactants in the self-healing reaction, and the ion complexing agent accelerates the progress of the self-healing reaction, so it can effectively improve the self-healing performance of the concrete material. The admixture can make the crack width of more than 0.4mm in the concrete material completely self-heal, effectively avoiding the external harmful substances from corroding the interior of the concrete structure along the cracks, causing safety problems such as durability degradation. Moreover, since the ion complexing agent can repeatedly undergo complexation-substitution reactions in the concrete material, the promoted crystallization self-healing material of the present invention has long-term effectiveness in improving the self-healing behavior of the concrete material, and cracks with a concrete age of more than 600 days can also be completely closed. In addition, compared with self-healing materials such as microcapsules and microorganisms, the promoted crystallization self-healing admixture of the present invention has the advantages of easy access to raw materials, simple construction, and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1-3 The graphs are the test results of the crack self-healing behavior of the self-healing cement-based composite materials prepared with different amounts of the crystallization-promoting self-healing concrete admixtures in Examples 1-3. Figure 3 These are the test results of long-term crack self-healing behavior of cement-based composites with a curing age of up to 620 days. DETAILED DESCRIPTION
[0030] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0031] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0032] Example 1
[0033] The amount of the crystallization-promoting self-healing concrete admixture in this embodiment is 1.5% of the total mass of cement and fly ash in the crystallization-promoting self-healing cement-based composite material.
[0034] in:
[0035] The crystallization-promoting self-healing concrete admixtures are calculated by weight and include: sodium hexametaphosphate: 0.04 parts, tetrasodium ethylenediaminetetraacetate: 0.88 parts, calcium formate: 4.4 parts, silica sol: 8.8 parts (mass fraction is 30%, purchased from Shandong Yousuo Chemical Co., Ltd.), and dispersible latex powder: 4.4 parts (ethylene-vinyl acetate copolymer, the molar ratio of ethylene and vinyl acetate is 1:1, purchased from Shandong Yousuo Chemical Co., Ltd.).
[0036] The promoted crystallization self-healing cement-based composite material includes, by weight: the above-mentioned promoted crystallization self-healing concrete admixture, P.O42.5 silicate cement: 494 parts (purchased from Harbin Cement Plant), fly ash: 741 parts, fine aggregate: 444 parts, water: 370 parts, polycarboxylic acid water reducer (purchased from Shanxi Feike New Materials Technology Co., Ltd.): 7 parts, and polyvinyl alcohol fiber: 26 parts (purchased from Japan Kuraray Co., Ltd.).
[0037] The specific steps of the self-healing cement-based composite material containing the crystallization-promoting self-healing admixture in this embodiment are as follows:
[0038] (1) The powdered raw materials of the crystallization-promoting self-healing concrete admixture are stirred and mixed uniformly by a blade mixer; then, the powdered raw materials are poured into a 3L stirring pot with cement, fly ash and fine aggregate, and slowly stirred at a speed of 65 r / min and 145 r / min for 3 minutes until the mixture is uniformly mixed;
[0039] (2) After mixing water and silica sol, slowly add the silica sol and the water reducing agent to the mixture of step (1), maintain the rotation speed in step (1) and stir slowly until the mixture becomes a fluid state, increase the stirring speed to 130 r / min, 290 r / min and maintain for 3 minutes until the mixture becomes a uniform fluid state;
[0040] (3) stirring at a low speed for 3 minutes at the stirring speed in step (1), and slowly adding the polyvinyl alcohol fiber. After the addition is completed, stirring at a high speed for 7 minutes at the stirring speed in step (2) until the fiber is completely dispersed;
[0041] (4) Pour the mixture into a mold, cover with plastic wrap for 24 hours, and then remove from the mold; and cure in a standard curing room at 20° C. and 90% humidity for 28 days.
[0042] Example 2
[0043] The amount of the crystallization-promoting self-healing concrete admixture in this embodiment is 3.0% of the total mass of cement and fly ash in the crystallization-promoting self-healing cement-based composite material.
[0044] in:
[0045] The crystallization-promoting self-healing concrete admixtures are calculated by weight and include: sodium hexametaphosphate: 0.1 parts, tetrasodium ethylenediaminetetraacetate: 1.8 parts, calcium formate: 8.8 parts, silica sol: 17.6 parts (mass fraction is 30%, purchased from Shandong Youso Chemical Co., Ltd.), dispersible latex powder (ethylene-vinyl acetate copolymer, the molar ratio of ethylene and vinyl acetate is 1:1, purchased from Shandong Youso Chemical Co., Ltd.): 8.8 parts.
[0046] The promoted crystallization self-healing cement material composition includes, by weight: the above-mentioned promoted crystallization self-healing concrete admixture, P.O42.5 silicate cement: 494 parts (purchased from Harbin Cement Plant), fly ash: 741 parts, fine aggregate: 444 parts, water: 370 parts, polycarboxylic acid water reducer (purchased from Shanxi Feike New Materials Technology Co., Ltd.): 7 parts, and polyvinyl alcohol fiber: 26 parts (purchased from Japan Kuraray Co., Ltd.).
[0047] The specific steps of the self-healing cement-based composite material containing the crystallization-promoting self-healing admixture in this embodiment are the same as those in Embodiment 1.
[0048] Example 3
[0049] The amount of the crystallization-promoting self-healing admixture in this embodiment is 4.5% of the total mass of cement and fly ash in the crystallization-promoting self-healing cement-based composite material.
[0050] in:
[0051] The crystallization-promoting self-healing concrete admixtures, calculated by weight, include: sodium hexametaphosphate: 0.14 parts, tetrasodium ethylenediaminetetraacetic acid: 2.6 parts, calcium formate: 13.2 parts, silica sol (mass fraction of 30%, purchased from Shandong Youso Chemical Co., Ltd.): 26.4 parts, dispersible latex powder (ethylene-vinyl acetate copolymer, the molar ratio of ethylene and vinyl acetate is 1:1, purchased from Shandong Youso Chemical Co., Ltd.): 13.2 parts.
[0052] The promoted crystallization self-healing cement material composition includes, by weight: the above-mentioned promoted crystallization self-healing concrete admixture, P.O42.5 silicate cement: 494 parts (purchased from Harbin Cement Plant), fly ash: 741 parts, fine aggregate: 444 parts, water: 370 parts, polycarboxylic acid water reducer (purchased from Shanxi Feike New Materials Technology Co., Ltd.): 7 parts, and polyvinyl alcohol fiber: 26 parts (purchased from Japan Kuraray Co., Ltd.).
[0053] The specific steps of the self-healing cement-based composite material containing the crystallization-promoting self-healing admixture in this embodiment are the same as those in Embodiment 1.
[0054] Figure 1-3 The figures are the test results of the self-healing behavior of cracks of cement-based composite materials containing different amounts of the crystallization-promoting self-healing concrete admixture in Examples 1 to 3. It can be seen from the figure that the crystallization-promoting self-healing concrete admixture provided by the present invention can effectively improve the self-healing performance of cement-based materials and can make cracks with a width of more than 0.4 mm in cement-based materials completely self-heal.
[0055] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A crystallization-promoting self-healing concrete admixture, characterized in that: The invention comprises, by weight, 485-520 parts of ion complexing agent, 2370-2380 parts of calcium formate, 4740-4760 parts of silica sol and 2370-2380 parts of dispersible latex powder.
2. The pro-crystallization self-healing concrete admixture according to claim 1, characterized in that: The ion complexing agent is 20-30 parts of sodium hexametaphosphate and 465-490 parts of tetrasodium ethylenediaminetetraacetate.
3. The crystallization-promoting self-healing concrete admixture according to claim 1, characterized in that: The silica sol is an alkaline nanometer-level silica solution, wherein the content of silica is 30±1%.
4. The crystallization-promoting self-healing concrete admixture according to claim 1, characterized in that: The dispersible latex powder is ethylene-vinyl acetate copolymer.
5. A crystallization-promoting self-healing cement-based composite material, characterized in that: The invention comprises, by weight, 2300 to 2400 parts of cement, 80 to 300 parts of the crystallization-promoting self-healing concrete admixture according to any one of claims 1 to 4, 3000 to 4000 parts of fly ash, 2000 to 2200 parts of fine aggregate, 30 to 35 parts of water reducing agent and 120 to 130 parts of polyvinyl alcohol fiber.
6. The promoted crystallization self-healing cement-based composite material according to claim 5, characterized in that: Also includes 1700 to 1800 parts of water.
7. The promoted crystallization self-healing cement-based composite material according to claim 5, characterized in that: The water reducer is a polycarboxylate water reducer; and the cement is ordinary Portland cement.
8. The method for preparing the promoted crystallization self-healing cement-based composite material according to claim 5, characterized in that: The following steps are involved: (1) mixing the powdered raw materials in the crystallization-promoting self-healing concrete admixture with cement, fly ash and fine aggregate; (2) adding a mixture of water and silica sol and a water reducing agent, and stirring until the mixture becomes a uniform fluid state; (3) Add the polyvinyl alcohol fibers while stirring at a low speed and stir rapidly until they are evenly dispersed.
9. The preparation method according to claim 8, characterized in that: In step (1), the stirring is performed at a revolution of 65±5 r / min and a rotation of 145±5 r / min; the stirring time is 2 to 4 min; In step (2), the stirring is performed at a revolution of 130±5 r / min and a rotation of 290±5 r / min; the stirring time is 2 to 4 min; In step (3), the low-speed stirring is 65±5 r / min of revolution and 145±5 r / min of rotation; the rapid stirring is 130±5 r / min of revolution and 290±5 r / min of rotation; the time of the low-speed stirring is 2 to 3 min; the time of the rapid stirring is 5 to 8 min.
10. Use of the crystallization-promoting self-healing concrete admixture according to any one of claims 1 to 4 in the preparation of a self-healing cement-based composite material.